Clinical Potential of Targeting Fibroblast Growth Factor‐23 and αKlotho in the Treatment of Uremic Cardiomyopathy. Issue 7 (9th April 2020) - Law, Jonathan P.; Price, Anna M.; Pickup, Luke; Radhakrishnan, Ashwin; Weston, Chris; Jones, Alan M.; McGettrick, Helen M.; Chua, Winnie; Steeds, Richard P.; Fabritz, Larissa; Kirchhof, Paulus; Pavlovic, Davor; et al.
Abstract: Chronic kidney disease is highly prevalent, affecting 10% to 15% of the adult population worldwide and is associated with increased cardiovascular morbidity and mortality. As chronic kidney disease worsens, a unique cardiovascular phenotype develops characterized by heart muscle disease, increased arterial stiffness, atherosclerosis, and hypertension. Cardiovascular risk is multifaceted, but most cardiovascular deaths in patients with advanced chronic kidney disease are caused by heart failure and sudden cardiac death. While the exact drivers of these deaths are unknown, they are believed to be caused by uremic cardiomyopathy: a specific pattern of myocardial hypertrophy, fibrosis, with both diastolic and systolic dysfunction. Although the pathogenesis of uremic cardiomyopathy is likely to be multifactorial, accumulating evidence suggests increased production of fibroblast growth factor‐23 and αKlotho deficiency as potential major drivers of cardiac remodeling in patients with uremic cardiomyopathy. In this article we review the increasing understanding of the physiology and clinical aspects of uremic cardiomyopathy and the rapidly increasing knowledge of the biology of both fibroblast growth factor‐23 and αKlotho. Finally, we discuss how dissection of these pathological processes is aiding the development of therapeutic options, including small molecules and antibodies, directly aimed at improving the cardiovascular outcomes of patients with chronic kidney disease and end‐stage renal disease.